Phase 1 Safety and Immunogenicity Study of a Quadrivalent Seasonal Flu Vaccine Comprising Recombinant Hemagglutinin-Flagellin Fusion Proteins. (29th January 2016) - Tussey, Lynda; Strout, Cynthia; Davis, Matthew; Johnson, Casey; Lucksinger, Gregg; Umlauf, Scott; Song, Langzhou; Liu, Ge; Abraham, Katalin; White, C. Jo
Abstract: Background.  We evaluated the safety and immunogenicity of VAX2012Q, a quadrivalent influenza vaccine comprising 4 hemagglutinin subunits fused to flagellin. Methods.  In this dose-ranging, open-label study, healthy adults (18–40 years) were divided into 7 cohorts for evaluation of 5 dose levels and 3 component ratios. Dose levels were as follows: (1) 1 mcg per component of VAX128C (H1N1), VAX181 (H3N2), VAX173 (B-YAM), and VAX172 (B-VIC), respectively; (2) 2 mcg per component, respectively; (3) 2, 4, 4, and 4 mcg of each component, respectively; (4) 2, 4, 6, and 6 mcg of each component, respectively; and (5) 3 mcg per component, respectively. Tolerability and immunogenicity data were analyzed. Results.  Three hundred sixteen subjects received VAX2012Q (309 per protocol). At all dose levels, 54% to 65% of subjects reported mild injection site pain, the most common local reaction. Moderate injection site pain increased at dose levels 2 through 5 (22%–42%, compared with 20% at dose level 1). Systemic symptoms were mostly mild to moderate with moderate symptoms increasing in dose levels 3 and 4. Three dose level 3 subjects (6%) reported severe, transient chills and or fever. Mean fold rises in hemagglutination inhibition titers ranged from 2.5 to 6.9 despite high baseline titers. Mean seroprotection rates were ≥90% and mean seroconversion rates were ≥40% for all strains in all groups postvaccination. Conclusions.  VAX2012Q elicited immune responses at all dose levels with no significant safety concerns. Doses of 2 or 3 mcg per component provided a favorable balance of tolerability and immunogenicity.